O ensino por projetos: um estudo da Feira Municipal de Investigação Científica - (:unkn) unknown (Universidade Federal do Pampa, 2016)
Scientific Research which involves project development for students of basic education in sciences fairs has been importantly because it provides experience exchange among students and strengthens the link between School and Community, the scientific knowledge and the interaction between teachers and students. In order to improve the multidisciplinary opportunities and social entre interaction between school and university, the extension project of UNIPAMPA – campus Dom Pedrito/RS entitled "Potentiating the Investigation in Natural Sciences in the School Space-Time and University in Southern Brazil" realized a Municipal Fair of Scientific Research in 2014. This fair covered 17 schools of this city. Considering its amplitude it was developed a screening of the type of search used in works, as well as the possible benefits no scientific participants. In this work, it was shown that research methodologies followed as projects arranged in as presented in literature according to Gil (2009), both in relation to the objectives and technical procedures were used in these elaborations, its enabling their categorization. In relation to the knowledge area used in researches, it was demonstrated a higher incidence in the natural sciences area, reinforcing that this area is the greater interest, being mostly inserted in the "Ecology and Environment", others analyzed works were found in other five different distributed knowledge areas (Chemistry, Physics, Interdisciplinary, Mathematics and Art). In the analysis of questionnaires given to teachers, it was found that the implementation of this fair improved teaching-learning process and contributed with positive effects in education development in this city. Thus, this fair provides an experience exchange spaces consolidation with scientific papers exhibition.
Keywords: Ensino de Ciências; Feira de Ciências; Tipos de pesquisa; Science Education; Science Fair; Types of Research; CNPQ::CIENCIAS EXATAS E DA TERRA